Land Reform in Sub-Saharan Africa: Exploring Interested Parties Perspectives on Cameroon's Land Tenure and Land Law Reform. - Kenfack Kenjio, Jacques Wilfried (Antioch University, 2023)
This research study seeks to understand interested parties’ perspectives on Cameroon's existing land tenure systems, the 1974 land law, and ongoing efforts to reform this land law. It identifies both concerns and specific recommendations from these parties on the formulation and implementation of future reforms. In the decades following the achievement of independence from European colonizers, most governments in sub-Saharan Africa (SSA) have adopted new national land tenure policies to meet their countries’ needs and aspirations. In some parts of SSA, however, this process of land tenure formalization has negatively impacted the land rights of people observing customary land tenure. This has been a result of government interventions such as compulsory land acquisitions, which while technically legal, are ethically questionable. In the face of this challenge, efforts to reform post-colonial land laws have become a matter of urgency. A national land reform process for Cameroon, announced in 2011 has adopted a multistakeholder approach. My study seeks to understand interested parties’ perspectives on Cameroon’s existing land tenure systems, the 1974 land law, and ongoing efforts to reform the land law. This study applied a case study methodological approach and a convergent mixed-method design. Evidence from this study shows that interested parties in Cameroon are in agreement on 1) the reform of the 1974 land law, 2) the recognition of customary land tenure, 3) the continued use of multistakeholder participation in land law reform, and 4) the promulgation of the new land law through mass sensitization and information dissemination.
URI: http://rave.ohiolink.edu/etdc/view?acc_num=antioch1684431556060359
Keywords: Government-Driven Land Dispossessions; Land Expropriations; Land Law; Land Reform; Land Tenure; Mixed Methods; Multistakeholder Participation; Sub-Saharan Africa

Overcoming Divergence in English and French Contract Law: A Common Taxonomy of Commercial Contracts - Pedamon, Catherine (University of Westminster, 2022)
The works presented for the PhD by publication are all connected in the way they engage in a functionally comparative study of the English and French law responses to common problems pertaining to contractual performance and contractual interpretation. My comparative inquiry demonstrates that both France and England have stayed true to their historic responses in times of peace and crisis confirming different mentalités juridiques. As neither England nor France offers ideal solution, parties may be better off finding a resolution to their disputes beyond the legal realm and respond to calls for collaboration. This nevertheless shows persisting differences in Anglo-French approaches. This thesis however argues that these divergences may nevertheless lead to common results through the lens of a taxonomy of commercial contracts – professionally drafted contracts may lead to converging results given the common application and interpretation of frequently used clauses beyond a domestic legal culture; by contrast, rudimentary contracts produce diverging results as the interpretation of these agreements is marked by a distinctive domestic socio-legal culture. This taxonomy has the potential to improve the predictability of outcomes in commercial disputes in England and France.
Keywords: Commercial contracts; Contract law; England; France

Challenges and solutions for the harmonisation of contract law within the BRICS countries. Invalidity of contracts and hardship - Veronese, Lígia Espolaor (Universidade de São Paulo, 2021)
The present thesis is concerned with a comparative study of contract law applicable in the BRICS countries Brazil, Russia, India, China and South Africa with a strong focus on the issues of invalidity of contracts and hardship. The purpose is to identify commonalities and divergences in these systems with different legal backgrounds, particularly the influence of civil law tradition in Brazil, Russia and China as opposed to common law in India, and the mixed system in South Africa. Among the identified divergences and challenges, the thesis purports to demonstrate that the obstacles are not insuperable and that there are rooms for the harmonisation and compatibility within the BRICS context with respect to the two selected topics of contract law. Even when full harmony is not reached, the research also purports to demonstrate that some countries may benefit from others divergent experiences. Detecting mutual contribution is of particular relevance to this group of countries, since they share the characteristic of being evolving systems which have undergone recent reforms in their legislation on contract law and may be more open to assess and incorporate more efficient contract practices.
Keywords: BRICS; Brazil; Common law vs. Civil law; Comparative law; Contract law; Contribuição; Contribution; Direito comparado; Direito contratual; Hardship; Harmonisation; Harmonização; Invalidade dos contratos; Invalidity of contracts; Russia; South Africa; Validade dos contratos; Validity of contracts

Selected legal aspects of liability insurance - Jacobs, Wenette (University of South Africa, 2020)
Liability insurance concerns an insured’s insurance of its legal liability towards a third party for the latter’s loss. This specialised type of insurance is rather neglected in South African insurance law. There is a lack of understanding of the intricacies of liability insurance and its unique challenges. This flows primarily from its complex nature as third-party insurance, which involves legal obligations between multiple parties, and a lack of statutory regulation of the distinctive contractual aspects of liability insurance. Furthermore, limited authority exists on contentious legal aspects as a result of the relatively small number of judicial decisions in this field of law. It is also evident that liability insurance constantly evolves as new grounds of liability emerge and new insurance products develop in response to the changing demands of society. The rise of consumerism and the increase in third-party claims amplify the economic significance of the law of liability insurance in South Africa. A substantial knowledge gap remains in our jurisprudence, irrespective of the recent introduction of new statutory instruments aimed at regulating insurance practice in general. These reforms have not as yet been applied critically to liability insurance, and no specialised legislation in South Africa regulates aspects of this branch of insurance as is the case with microinsurance. The focus in this thesis is on two main issues: the insurer’s duty effectively to indemnify the insured, and the insurer’s defence and settlement of third-party claims brought against the insured. As a subsidiary theme, this thesis analyses legal uncertainties that may persist during pre-contractual negotiations, the liability insurance contract lifecycle, and even after the expiry of the contract. Legal challenges can be addressed by novel and creative application of the national law. Potential solutions can be gleaned from the other progressive jurisdictions reviewed – English and Belgian law. It is evident that this research may prompt Parliament to develop specific rules and regulations for liability insurance contract law. This thesis includes a check list of some of the most important disclosure duties for procuring liability insurance cover, its operation, and claims processes.
Keywords: Claims-made policy; Duty to indemnify; Indemnity insurance; Liability insurance; Liability insurer; Third-party insurance